Trust and Tax Morale: The Role of Governance Quality, Institutional, Media Campaigns - Astri Warih Anjarwi (Jurnal Akuntansi dan Keuangan, 2025)
Institutional theory posits that the interaction of governance quality and institutional factors within both organizational and societal contexts shapes tax morale. Trust plays a key role at both interpersonal and institutional levels, enhancing tax morale and compliance. In today’s information age, the media significantly influences opinions and norms related to tax ethics. This study explores the mediating role of trust between governance quality and institutional determinants of tax morale, while also examining the moderating effect of media campaigns on this relationship, filling a gap in the literature. Using a survey of 418 individual taxpayers, the study finds that trust significantly mediates the effects of governance quality and institutional factors on tax morale. However, media campaigns show limited effectiveness in moderating the impact of trust on tax morale. These findings emphasize the importance of trust in shaping tax morale and highlight its potential as a strategic tool for enhancing tax compliance and ethical tax behavior.